My Google Chromebook - Miller, Michael, 1958- (Que, 2016)
"'My Chromebook, Third Edition' is the one-stop guide to Chrome OS and Google Chromebooks. It has been updated to cover the latest version of Chrome OS, including the new desktop, and the latest Chromebook and Chromebox models. It starts with basic unboxing and configuration and works through customization, cloud storage, Chrome Apps, and troubleshooting."--Publisher annotation.